Dynamic Thin Markets - Rostek, Marzena; Weretka, Marek (Review of Financial Studies, 2015)
Large institutional investors dominate many financial markets. This paper develops a consumption-based model of markets in which all institutional traders recognize their impact on prices. Bilateral (buyer and seller) market power changes efficiency and arbitrage properties of equilibrium. Predictions match temporary and permanent price effects of supply shocks, order breakup, limits to arbitrage, nonneutrality of trading frequency, and real effects of shocks and announcements in periods other than event dates. Maximizing welfare and stabilizing liquidity through disclosure of information about fundamentals presents a trade-off. Equilibrium representation as "trading against price impact" provides a link with the industry's practice.